Improving Entrepreneurial Skills in Portugal Higher Education - a case study in Alto Minho Region - Rodrigues, Helena Sofia (2017)
The entrepreneurship topic is identified as a switch gear to enhance the economic growth and as an important driver for the society transformation. In particular, it should be used as a counter response strategy to the current crisis and as a means to combat apathy, inertia, and the lack of entrepreneurial initiative. It is known that entrepreneurship education increase self-reported intentions to begin a business. The biggest challenge in higher education is the breaking of traditional studies methods, where students and their families think in create new employees for other companies and not to create a new employer. Entrepreneurship education aims to produce graduates with a set of skills and an entrepreneurial mindset, in order to come up with original ideas in response to identified market shortfalls and needs. At Business School of the Polytechnic Institute of Viana do Castelo, an integrated set of projects and activities are trying to contribute to the improvement of entrepreneurial skills of the region: since workshops open to community, to individual projects of students to prepare a startup company, they have been contribute to enhance new capacities and a better entrepreneurial identity of students. Some of the objectives of these integrated initiatives refer to: develop the ability to apply concepts and theories covered during the graduation in an integrated manner and providing them the opportunity to confront the theories studied with existing professional practices aimed at consolidation experience and professional performance; fill specific gaps in areas considered relevant to the progression and development of their future professional activity; provide a practical view of business reality through the ideas with potential formulation for the preparation of business plans and marketing; provide students tools for implementation, monitoring and proper business management; encourage the entrepreneurial spirit and an ethical culture and proactive by implementing projects that lead to the solution of problems and improvements of organizational processes.